Answer:
Step-by-step explanation:
[tex]\bold{slope\, (m)=\dfrac{change\ in\ Y}{change\ in\ X}=\dfrac{y_2-y_1}{x_2-x_1}}[/tex]
(0, 2) ⇒ x₁ = 0, y₁ = 2
(-4, 1) ⇒ x₂ = -4, y₂ = 1
So the slope:
[tex]\bold{m=\dfrac{1-2}{-4-0}=\dfrac{-1}{-4}=0.25}[/tex]
The point-slope form of the equation of the line passing through point (x₀,y₀) and with slope m is: y - y₀ = m(x - x₀)
m = 0.25
(0, 2) ⇒ x₀ = 0, y₀ = 2
Therefore:
y - 2 = 0.25(x - 0)
y - 2 = 0.25x {add 2 to both sides}
y = 0.5x + 2 ← the slope-intercept form of the equation